Does kV Image Guidance for Bone Metastases Improve Pain Control? - Tunceroglu, Ahmet S.; Gui, Bin; Lu, Shou-En; Sison, Julian; Parikh, Rahul; Goyal, Sharad; Haffty, Bruce G.; Kim, Sung; Jabbour, Salma K. (Frontiers in Oncology, 2021)
Purpose/Objectives Despite its widespread availability, the use of kilovoltage (kV) image guidance is often related to factors such as perceived adequacy of clinical patient setup and individual practice patterns. We sought to determine whether kV image guidance in the treatment of painful bone metastases would improve therapeutic efficacy. Materials/Methods Under an Institutional Review Board approved protocol, hospital records of 164 patients having received radiation therapy to 257 individual painful osseous metastases were retrospectively reviewed. Marginal logistic regression analyses using the generalized estimating equation (GEE) approach were used to investigate potential associations between pain reduction and several patient, disease, and treatment related variables. Correlation of kV image guidance with pain reduction was analyzed by univariate and multivariate GEE logistic regression analysis. Results Median time to pain reduction was 3 days (range 0 109 days) from the start of radiation therapy. Pain reduction ≥ 50% was noted in 196 (77%) metastatic lesions with 136 (53%) demonstrating complete pain relief. Patients with metastatic lesions from non-small cell lung cancer experienced less pain relief (p = 0.007). Disease extension outside of bone was a negative predictor for pain reduction (p = 0.02). On univariate and multivariate logistic regression, kV image guidance demonstrated a statistically significant correlation with improved pain control in cases involving treatment of the lower extremities (p = 0.03) and those with fewer treatment fractions (p = 0.01), particularly in the setting of extra-osseous disease extension (p = 0.003). Conclusions Kilovoltage image guidance in the treatment of painful bone metastases may offer greater pain control through improved patient setup, particularly for patients with tumors of the lower extremities, extraosseous disease extension, and fewer treatment fractions.